Modeling and simulation of hydraulic buffering valve for power-shift transmission - Drakulić, Momir M.; Đurić, Aleksandar S.; Ponorac, Luka M.; Benmeddah, Abdeselem B.; Perić, Sreten R. (Vojnotehnički glasnik / Military Technical Courier, 2023)
Introduction/purpose: The hydraulic buffering valve has the greatest influence on the dynamic characteristics of power-shift transmission. The hydraulic buffering valve is a transmission element that controls increase in pressure in friction assemblies during the gear shifting process. By choosing the optimal control of pressure increase during shifting, reduction of dynamic loads in gear transmissions and thermal loads in friction assemblies is achieved. Methods: The paper analyzes the principle of one of hydraulic buffering valve solutions as well as the influence of certain parameters on the control of pressure increase. After the analysis of the working principle of the hydraulic buffering valve, a simulation model was developed in the MATLAB/Simulink software package. Results: The results obtained using the simulation model were compared with the experimental results of the selected pressure modulator solution. The selected hydraulic buffering valve was developed as part of the development of a device for power-shift transmission. The simulation results showed a satisfactory match with the experimental results. Conclusion: The developed simulation model enables a relatively easy and quick change of the parameters of the hydraulic buffering valve as well as a possibility of a faster and better understanding of the influence of individual parameters on pressure increase during the gear shifting process.